Chicken Peripheral Blood Mononuclear Cells Response to Avian Leukosis Virus Subgroup J Infection Assessed by Single-Cell RNA Sequencing - Qu, Xiaoyun; Li, Xiaobo; Li, Ziwei; Liao, Ming; Dai, Manman (Frontiers in Microbiology, 2022)
Chicken peripheral blood mononuclear cells (PBMCs) exhibit wide-ranging cell types, but current understanding of their subclasses, immune cell classification, and function is limited and incomplete. Here we performed single-cell RNA sequencing (scRNA-seq) of PBMCs in Avian leukosis virus subgroup J (ALV‐J) infected and control chickens at 21 days post infection (DPI) to determine chicken PBMCs subsets and their specific molecular and cellular characteristics. Eight cell populations and their potential marker genes were identified in PBMCs. T cell populations had the strongest response to ALV-J infection, based on the detection of the largest number of differentially expressed genes (DEGs), and could be further grouped into four subsets: activated CD4+ T cells, Th1-like cells, Th2-like cells, and cytotoxic CD8+ T cells. Furthermore, pseudotime analysis results suggested that chicken CD4+ T cells could potentially differentiate into Th1-like and Th2-like cells. Moreover, ALV-J infection activated CD4+ T cell was probably inclined to differentiate into Th1-like cells. Compared to the control PBMCs, ALV-J infection also had an obvious impact on PBMCs composition. B cells showed inconspicuous response and their numbers decreased in PBMCs from ALV-J infected chicken. Proportions of cytotoxic Th1-like cells and CD8+ T cells increased in the T cell population of PBMCs from ALV-J infected chicken, which were potentially key mitigating effectors against ALV-J infection. More importantly, our results provide a rich resource of gene expression profiles of chicken PBMCs subsets for a systems-level understanding of their function in homeostatic condition as well as in response to viral infection.